Efficiency enhancement of perovskite solar cells via incorporation of phenylethenyl side arms into indolocarbazole-based hole transporting materials. Issue 16 (13th April 2016) - Petrikyte, Ieva; Zimmermann, Iwan; Rakstys, Kasparas; Daskeviciene, Maryte; Malinauskas, Tadas; Jankauskas, Vygintas; Getautis, Vytautas; Nazeeruddin, Mohammad Khaja
Abstract : Small-molecule HTMs based on an indolocarbazole core were synthesized and incorporated into perovskite solar cells, which displayed a PCE up to 15.24%. Abstract : Small-molecule hole transporting materials based on an indolocarbazole core were synthesized and incorporated into perovskite solar cells, which displayed a power conversion efficiency up to 15.24%. The investigated hole transporting materials were synthesized in three steps from commercially available and relatively inexpensive starting materials without using expensive catalysts. Various electro-optical measurements (UV-vis, CV, hole mobility, DSC, TGA, ionization potential) have been carried out to characterize the new hole transporting materials.